The impact of the of the COVID-19 pandemic on training and motivational behavior: A survey of children and adolescents - Kalski, L.; Bauerecker, I. L.; Jarius, L.; Hafermann, L.; Wolfarth, B. (Deutsche Zeitschrift für Sportmedizin, 2023)
Summary